Cover Feature: Tuning the Selectivity of AuPd Nanoalloys towards Selective Dehydrogenative Alkyne Silylation (Chem. Eur. J. 23/2019). Issue 23 (25th March 2019) - Wissing, Maren; Studer, Armido
Abstract : It takes two to tandem ! Tailor‐made AuPd nanoalloys were developed for the selective cross‐dehydrogenative coupling of terminal alkynes and hydrosilanes. Although monometallic Au nanoparticles do not catalyze that transformation, monometallic Pd nanoparticles show low selectivity for the desired alkynylsilane. The catalyst with cooperatively interacting Au and Pd metals tolerates a large number of functional groups and works at room temperature under air atmosphere. More information can be found in the Communication by M. Wissing and A. Studer onpage 5870 .